Situational indicators of team efficacy in group phase of football Championship League - Novak, M.; Basic, D.; Tomasko, J.; Barisic, V. (Acta Kinesiologica, 2015)
Basic goal of this paper was to establish differences between teams depending on their final rankings in a group phase of competition. 32 teams were analyzed throughout 96 total games in group phase of 2014/2015 Football Championship League. Variables compared were ball passes; ball passes considering field zone, distance, and direction; goal strikes; dribbling; center shots; corners; taking the ball; aerial duels; and fouls. T-testing independent samples showed that teams who were better positioned in the end of group phase had greater values in number of passes, number of passes in the last third of the field, and the number of successful passes in the last third of the field.